STRENGTHENING THE ROLE OF VILLAGES THROUGH PARTICIPATORY RURAL APPRAISAL METHOD TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS - Rayyani, Wa Ode; Idrawahyuni, Idrawahyuni; Wahyuni, Nia; Salam, Silviana (Universitas Muhammadiyah Mataram, 2024)
Abstract: This community service aims to strengthen the village in achieving SDGs. The strengthening focuses on two aspects: empowering the rural community's economy and increasing the community's understanding of the importance of education. This activity takes place in Desa Balangtanaya, Kecamatan Polombangkeng Utara, Kabupaten Takalar, Sulawesi Selatan. PRA approach is utilized as the method for this activity, which is a participatory approach used in community-based development in rural areas. The PRA method involves three stages: (a) direct observation; (b) FGD; and (c) guidance and mentoring for one month. The benefits of this community service include strengthening the village's economy and improving the community's knowledge of education. The partners in this activity are the Balangtanaya Village community, consisting of 30 participants including Bumdes managers, PKK women, and community members. Evaluation is conducted through direct monitoring, interviews, and analysis of activity outcomes. The achieved results include a 20% increase in education knowledge (softskill) and a 15% increase in the village's economic value (hardskill).